2012
DOI: 10.1186/1746-1596-7-172
|View full text |Cite
|
Sign up to set email alerts
|

A case of enteropathy-associated T-cell lymphoma (Type I) arising in stomach without refractory celiac disease

Abstract: Enteropathy-associated T-cell lymphoma (EATL) is a rare peripheral T-cell lymphoma which was classified into 2 types based on histology. EATL is often, but not always, associated with celiac disease. EATL type I is a large cell lymphoma which is more common in frequency and highly associated with celiac disease compared with type II. Jejunum and ileum are the common sites, although EATL can rarely occur in the duodenum, stomach and colon or outside the gastrointestinal tract. We herein presented one case of ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Further, H. pylori infection correlates with MALT lymphoma, and MALT lymphomas express B-cell lineage markers. 8 However, in the present case CD138 immunostaining was positive and a Giemsa stain was negative. Some studies have reported the complete regression of EMPs after treatment for H. pylori .…”
Section: Discussioncontrasting
confidence: 54%
“…Further, H. pylori infection correlates with MALT lymphoma, and MALT lymphomas express B-cell lineage markers. 8 However, in the present case CD138 immunostaining was positive and a Giemsa stain was negative. Some studies have reported the complete regression of EMPs after treatment for H. pylori .…”
Section: Discussioncontrasting
confidence: 54%
“…In absence of mass formation, EATL can be confused with an inflammatory ulcer, but the presence of atypical cells in EATL excludes this diagnosis (10,11). B cell lymphomas, poorly differentiated carcinomas, and benign lesions were excluded in our case with the presence of monomorphic atypical tumor cells stained positively for T lymphocyte markers.…”
Section: Discussionmentioning
confidence: 94%
“…EATL type I possesses large or pleomorphic cells that are express CD3, partially express CD30, but usually do not express CD8 and CD56. EATL also lacks EBV RNA expression in an EBER in situ hybridization ( 15 ).…”
Section: Discussionmentioning
confidence: 99%